„Tubylec tubylcowi nierówny”. Przyszli nauczyciele o uczeniu się w epoce cyfrowej - Lidia Bielinis; Cezary Kurkowski; Monika Maciejewska (Problemy Wczesnej Edukacji)
In the study we present results of two research projects conducted simultaneously at the Faculty of Social Sciences, UWM in Olsztyn referring to the place digital technologies have in the learning processes in the opinions of Early Education students. The results show that the group of surveyed students might be situated on the borderline of digital natives and digital immigrants’ worlds. The conducted survey demonstrated limited trust to digital sources of knowledge amongst students and discrepancy between their personal experiences with using new technology, on a daily basis, and traditional ways of learning proposed by the University. The analysis of the case study indicated that for preparing future teachers to work with children (digital natives), it is important to organize a learning environment in which both worlds – digital and analogue – are connected.